Design and optimization of passive residual heat removal system for lead‐bismuth reactor SVBR‐100. (8th November 2020) - Li, Xinyu; Cheng, Jie; Zhang, Dalin; Dai, Zhiwen
Summary: The passive residual heat removal system (PRHRS) is of great significance to ensure the safety of small modular reactors. In this work, a PRHRS based on the reactor pressure vessel was designed and optimized for the lead‐bismuth reactor SVBR‐100 and an one‐dimensional transient analysis code transient analysis codes for LBE reactor was developed as well. The uncertainty analysis was carried out to identify and optimize the key parameters affecting PRHRS, based on the one‐dimensional physical fields obtained from the primary loop and evaporator. The results of transient calculation showed that the designed PRHRS can effectively remove the heat of the core under the accident of unprotected loss of flow and the station blackout (SBO). The results of sensitivity analysis showed that the maximum temperature of lead‐bismuth eutectic (LBE) was strongly positively correlated with heat capacity and thermal conductivity of the cladding, and was moderately positively correlated with the kinetic coefficient of the pump; The medium negative correlation factor of peak pellet temperature (PPT), peak cladding temperature (PCT), and maximum LBE temperature was the diameter of the sleeve of PRHRS, and therefore, increasing the diameter of the sleeve can improve the performance of the system. The results of uncertainty quantification showed that the output uncertainties of PPT and PCT were larger than those inputs. The uncertainty of LBE temperature was very low, and all thermal parameters in SBO were within safe limits. Finally, the optimized parameters of PRHRS were obtained. This work can provide a reference for the development of designing PRHRS and relevant transient calculation codes for small modular LBE reactors. Abstract : In this work, a PRHRS based on SVBR‐100 was designed, and the transient analysis codes TACLR were developed as well. Sensitivity analysis and uncertainty quantification were performed for optimization and evaluation. The results showed that the PRHRS can effectively work under the ULOF and the SBO. Some key parameters were identified and the uncertainties were evaluated. This work can provide a reference for the development of designing PRHRS and transient analysis codes for small modular LBE reactors.